FOREIGN PRACTICE OF VOCATIONAL AND CAREER DEVELOPMENT OF CIVIL SERVANTS - A. Suvorov (Вестник университета)
The article presents the analysis of foreign experience in the field of vocational and career development of civil servants. It is shown that the basis for professional and career growth of civil servants lies with the dominant model of civil service: Romano-Germanic model (career), the Anglo-Saxon model (positional), the model of civil service of the countries of Islamic orientation, labor model. Comparative characteristic of the professional career development of civil servants in Russia and abroad. On the basis of generalization of the results of the analysis the conclusions about the advantages and disadvantages of foreign practices, but also about the possibility of using international experience in Russian conditions.